Analisis Pengaruh Pemahaman Mahasiswa Pada Wadiah Dan Bagi Hasil Terhadap Minat Menjadi Nasabah Bank Syariah (Studi Kasus Pada Mahasiswa FEB UNISMA) - Yeni Kurniati; Noor Shodiq Askandar; Afifudin Afifudin (El-Aswaq: Islamic Economics and Finance Journal, 2021)
This study aims to determine the effect of understanding on wadiah and profit sharing on interest in becoming a customer of a sharia bank. this type of research is quantitative research. In this study, the sample taken was FEB UNISMA students starting from the 2017-2020 class, totaling 100 people. Taking the number of samples using the Slovin formula. The analytical tool used is Multiple Linear Regression Analysis using SPSS 16. The results showed that the variable Wadiah (X1) had a positive and partially significant effect on student interest (Y), profit sharing (X2) had a positive and significant effect on partial to student interest (Y)..